Damage Evaluation of Masonry Buildings after Van Earthquakes in 2011 - Guney, D.; Kuruscu, A. O.; Arun, G. (TAYLOR & FRANCIS INC, 2016)
In 2011, Van City, located in southeast Turkey, was hit by two destructive earthquakes that caused the loss of life and property. During these earthquakes approximately 4,000 buildings collapsed or were seriously damaged, 644 people were killed, and 2,608 people were injured. In the region hit by the earthquakes there were many houses and public buildings constructed with stone, brick, adobe, and concrete blocks, some of which were heavily affected while others incurred only slight damage. Most of the buildings in the region were built without any design, control, or supervision. In this article, the relationship between damage levels and structural parameters, such as the age of a building, masonry material, construction method, and workmanship quality, affecting the seismic performance of the masonry buildings of this area are evaluated based on site investigation following the earthquakes. This article also includes an overview of the dynamic characteristics of the earthquake and the seismic history of the region.
Keywords: adobe; damage assessment; failure mechanism; seismic performance of masonry buildings; Van earthquake; vernacular masonry buildings; Architecture; Construction & Building Technology; Engineering